2017
DOI: 10.1111/cch.12438
|View full text |Cite
|
Sign up to set email alerts
|

Parental influences on weight‐related health behaviors in western and eastern cultures

Abstract: This study provides evidence that the development of life-long health behaviors that contribute to BMI are significantly influenced by parents' behaviors and parenting styles. Moreover, an interaction of parental characteristics and cultural norms is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…A further consideration is parental factors, which are known to be determinants of children's dietary patterns. Previous studies indicated that food practices [59], health concerns and parental BMI [60], and parenting styles [61,62] were associated with unhealthy dietary outcomes in children. Food environment at home and school are critical in the diet quality for school-aged children as their eating pattern are not self-sufficient [60,63,64].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A further consideration is parental factors, which are known to be determinants of children's dietary patterns. Previous studies indicated that food practices [59], health concerns and parental BMI [60], and parenting styles [61,62] were associated with unhealthy dietary outcomes in children. Food environment at home and school are critical in the diet quality for school-aged children as their eating pattern are not self-sufficient [60,63,64].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It is generally accepted that an individual’s attitude toward his/her body image is rooted in social cognition and culture [ 12 , 13 , 14 ]. China is largely influenced by communist ideology, Confucian, and later Neo-Confucian orientation [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that individuals’ attitude toward their body image is rooted in their social cognition and culture [ 12 , 13 , 14 , 15 ]. While western culture emphasizes individual responsibility in different life domains, including self-management and weight control [ 16 ], this is less highlighted in the Eastern cultures.…”
Section: Introductionmentioning
confidence: 99%
“…• Parenting styles and behavior: Parenting styles and behavior have an influence on developing the life-long health habits [7] • Socio-cultural factors: Social customs and norms in the communities, family members and caregivers can influence the child's eating habits, impacting their growth [8] • Environmental factors: UNICEF 2019 review reflected that easy access to safe drinking water and improved individual household sanitation can reduce the infection risk, malabsorption, malnutrition and mortality [9] • Maternal and Child nutrition: UNICEF reported in 2018 that improvements in maternal and child nutrition, and healthy environment could improve child's nutritional status, growth and development [9].…”
Section: Factors Impacting Growth and Development Of Preschoolersmentioning
confidence: 99%